Functional and cognitive capacity differ in dystonic motor subtypes when compared to choreatic and hypokinetic‐rigid motor subtypes in Huntington's disease - Achenbach, Jannis (Brain Behav, 2020)
BACKGROUND: Motor phenotypes in Huntington's disease vary manifold. Phenotype classification is essential to adapt treatment. The aim of this study was to classify a dystonic subtype closer. METHODS: A total of 7,512 manifest ENROLL‐HD participants were subdivided into mainly choreatic (N = 606), dystonic (N = 402), and hypokinetic‐rigid (N = 369) subjects. Cognitive (verbal fluency, symbol digit, stroop color, trail making, Mini‐Mental State Examination), functional (total functional capacity, Independence Scale), and psychiatric (problem behaviors assessment, Hospital Anxiety and Depression Scale) performance was evaluated at baseline visit. RESULTS: Symptoms onset for dystonic were similar to hypokinetic‐rigid, but earlier compared to choreatic subjects (p < .001). Cognition was better in both groups compared to hypokinetic rigid (all p < .001). Functionality differed between all groups (all p < .001). Differences remained (all p < .001) after controlling for CAP score, CAG, age, disease duration, and education. CONCLUSIONS: Motor subtypes differ in functional and cognitive capacities but less in psychiatric. We identified better cognitive and functional capacities and similar onsets in predominant dystonic compared to hypokinetic‐rigid patients.